Achieving Residential Coastal Communities Resilient to Tropical Cyclones and Climate Change - Adhikari, Pramodit; Abdelhafez, Mohamed A.; Dong, Yue; Guo, Yanlin; Mahmoud, Hussam N.; Ellingwood, Bruce R. (Frontiers in Built Environment, 2021)
Coastal cities in the Southeast and Gulf Coast of the United States are at increasing risk from tropical cyclones (hurricanes) due to the combined effects of urbanization, rapid economic development and climate change. Current building codes and standards focus on minimum performance criteria for individual buildings exposed to severe hazard events to ensure occupant safety. However, they do not consider the resilience of buildings and building portfolios, which are key factors in determining whether a community can respond to and recover from a severe natural hazard event. Light-frame wood residential buildings dominate the residential market in the U.S., represent a significant percentage of the investment in the built environment, and are especially vulnerable to hurricane winds and storm surge in coastal areas. Our study of the impact of various hurricane and climate change scenarios on the performance of coastal residential communities reveals that decision-making at the community level is needed to develop rational engineering and urban planning policies to mitigate the impact of hurricane wind and storm surge and to adapt to climate change, and suggests that fundamental changes in the current building regulatory process may be necessary.